Pembinaan Moderasi Beragama di Desa Pantai Labu Pekan - Wulan Purnama Sari Vinia; Mhd. Fajar Siddik; Indra Ma’aruf Kusniadi; Meisya Adelia; Mhd. Furqan Amal (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This paper focuses on the results of the Regular KKN activities that take the theme of religious moderation. This Regular KKN is a real service around the residents located in Pantai Labu Pekan Village. This KKN activity was carried out in order to make a concrete contribution in building religious moderation in Pantai Labu Pekan Village. Seen in brief, moderate attitudes in religion can be achieved by prioritizing balance, controlling emotions so as not to be excessive, and also being careful in acting on religious matters. Can Regular KKN activities have an influence on religious moderation in Pantai Labu Pekan Village, then what activities can affect religious moderation. Facing diversity, it takes what is called an attitude of moderation. The form of this moderation attitude can of course differ from one place to another. Moderation is synonymous with acknowledging the existence of other parties, having a tolerant attitude, respect for differences of opinion, and not imposing the will of others. Keywords : Religious Moderation, Tolerance